REALITIES OF UKRAINE’S ADAPTATION TO THE COMMON MARKET OF THE EUROPEAN UNION - RUMYANTSEV, Anatolii; YAREMOVYCH, Petro; KOVBYCH, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the state, features, parameters of the leading directions of economic interaction of Ukraine with the common market of the European Union (EUCM) in modern conditions. The main prerequisites that determine the specifics of the formation of the current realities of Ukraine’s adaptation to the EUCM are highlighted, namely: a) intensification of globalization processes covering the world economy in the direction of liberalization of international economic relations, use of the advantages of digitalization, as conditions for their transition to a qualitatively higher level of functioning; b) loss of domestic export potential, import opportunities, labor resources as a result of russian aggression against our country. The economic essence of the EUCM is determined, which consists in the harmonious supply of goods, capital, labor, services and the demand for them by the EU member states under the conditions of free export-import operations. As the main realities that recognize the stability of Ukraine’s adaptation to the EU, modern directions and features of our country’s mutual trade with the EU are considered, taking into account the feasibility of clearly observing the provisions of the DCFTA agreement, the state of functioning of the domestic international transport infrastructure, as conditions for ensuring foreign trade, the growth of the scale of forced , as a result of the war, emigration to the EU, of our compatriots, in particular, the active workforce, which adapts to the EU labor market and is considered one of the structural links of the EUCM. In the context of digitalization of the EUCM, the tendency to increase the supply of Ukrainian highly qualified specialists, including in the JSC sphere, on the EU labor market and the possibility of using their digitalization potential on a remote basis are analyzed. The prospective reality of Ukraine’s adaptation to the EUCM is determined by the need to use the advantages that our country acquired from obtaining the status of a candidate for EU membership.